Public and private provision of infrastructure and economic development - Andrew Bernard; Márcio Gomes Pinto Garcia (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1997)
This paper examines the role of infrastructure in long run economic growth. The paper consists of two sections, the first concentrates on the theoretical role of government spending in models of growth and the second details examples of private participation in infrastructure development. Using a simple endogenous growth model we find that while the hypothesized benefits of infrastructure expenditures may be large they require care in matching appropriate financing. As the development and maintenance of infrastructure will continue to be pivotal to the long term success of growing economies, we emphasize the lessons on financing and the caveats of private participation to those who are exploring innovative mechanisms for infrastructure design.
Keywords: 330